2020
DOI: 10.1007/s10997-020-09537-7
|View full text |Cite
|
Sign up to set email alerts
|

Going concern modifications and related disclosures in the Italian stock market: do regulatory improvements help investors in capturing financial distress?

Abstract: This paper investigates the investor reaction to audit reports containing a going concern modification (GCM) in the Italian market following new amendments regarding auditing regulations and public financial information disclosures. We applied the event study (ES) methodology to short event windows considering Italian listed companies during the period 2009–2015. Our findings partially contradict previous studies revealing a systematic negative impact of GCMs, especially when a GCM is attached to unqualified o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 64 publications
1
7
1
1
Order By: Relevance
“…The significant association between Age and Success (Column 1) not only confirms the evidence of Kim and Kim (1999) but is also in line with the results of Åstebro and Winter (2012), who demonstrate that age is positively and significantly associated with the probability that a distressed company exits financial distress. Column 1 shows that the coefficient of GC is positive and significant at the 5% level, indicating that audit opinions without going concern modifications are associated with a higher probability of confirmation, in line with the findings of Brunelli et al (2021). Moreover, the coefficient of NI_growth , as reported in Column 1, is negative and slightly significant.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…The significant association between Age and Success (Column 1) not only confirms the evidence of Kim and Kim (1999) but is also in line with the results of Åstebro and Winter (2012), who demonstrate that age is positively and significantly associated with the probability that a distressed company exits financial distress. Column 1 shows that the coefficient of GC is positive and significant at the 5% level, indicating that audit opinions without going concern modifications are associated with a higher probability of confirmation, in line with the findings of Brunelli et al (2021). Moreover, the coefficient of NI_growth , as reported in Column 1, is negative and slightly significant.…”
Section: Resultssupporting
confidence: 65%
“…We consider the annual change in net income as a control variable ( NI_growth ) to account for the loss of profitability, and we include the presence of Big4 auditors ( Big4 ) to measure the potential Big N effect. Brunelli et al (2021) demonstrated that investors react negatively to unqualified and qualified audit opinions with going concern modifications. According to the revised ISA 570, if the financial statements provide sufficient information regarding the auditee’s ability to continue as a going concern, auditors must express their doubts in the emphasis of matter paragraph.…”
Section: Methodsmentioning
confidence: 99%
“…The outcome indicates that going concern does not mediate the relationship between financial reporting and investor confidence. This result contradicts Brunelli, Carlino [ 28 ] and Mohamed, Allini [ 29 ], who discovered that going concern has a mediating effect.…”
Section: Discussioncontrasting
confidence: 63%
“…Brunelli, Carlino [ 28 ] conducted research in the Italian market to determine how investors react to audit reports that contain a going concern modification. This research made use of a technique known as event study in order to investigate the brief event windows experienced by Italian-listed firms between the years 2009 and 2015.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Financial distress is an event of a continuous decline in the company's financial performance within a particular time (Brunelli et al, 2021). For companies, financial distress is one of the conditions that cause bankruptcy.…”
Section: Financial Distressmentioning
confidence: 99%